2013
DOI: 10.1002/anie.201210080
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Energy Levels of Semiconductor Nanocrystals by a Dopant Approach

Abstract: The energy levels of semiconductor nanocrystals (NCs) are among the key factors controlling the performance of solar cells [1][2][3][4][5][6] and optoelectronics devices. [7][8][9] Therefore, an accurate determination of the conduction band (CB) and valence band (VB) of the NCs is important and a prerequisite in rational design of the building blocks using the NCs. The energy levels of the NCs are acquirable by X-ray absorption, [10] photoelectron, [11][12][13][14] or scanning tunneling spectroscopy.[15] Theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
1
22
0
1
Order By: Relevance
“…Monovalent doping, for example with Ag + and Cu + ions, has been the subject of research by many groups, because it provides not only color‐center impurities, but also extra holes for electronic‐impurity doping . It could be concluded that different synthesis and doping methods usually enabled different kinds of doping level and dopant location in the NC matrix.…”
mentioning
confidence: 99%
“…Monovalent doping, for example with Ag + and Cu + ions, has been the subject of research by many groups, because it provides not only color‐center impurities, but also extra holes for electronic‐impurity doping . It could be concluded that different synthesis and doping methods usually enabled different kinds of doping level and dopant location in the NC matrix.…”
mentioning
confidence: 99%
“…Here, the Mn d‐ states are labeled following the reports of refs. The Cu position was determined from the PL spectra of codoped QDs . CB and VB refer to the abbreviations of conduction and valence bands, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…15 16 Dilute Cu doping introduces a single atomic-like energy level in between the CB and VB of the host material. The atomic-like nature of this level shields it from the energy variations arising due the band broadening, strain within the lattice and other solid state effects.…”
mentioning
confidence: 99%